Improving Operational Energy Efficiency in the Acetaldehyde Production Process Through the Addition of a Heat Exchanger and Optimization of Heat from Reactors' Outlet - Balqist Nazlia; Fitri Muthiah Fahira; Helena Novita Hapsari; Pricellia Alexandra Natasya Putri; Kanya Gading Adyawita (Journal of Chemical Engineering Research Progress, 2026)
Enhancing the energy efficiency of acetaldehyde production is essential for advancing operational performance and supporting sustainable chemical manufacturing. This study investigates the effect of integrating an additional heat exchanger into the ethanol dehydrogenation flowsheet, positioned before the feed stream enters the process unit, on overall thermal efficiency. Thermodynamic simulations were conducted to compare the baseline configuration with the modified design. The added heat exchanger recovers energy from existing process streams, thereby reducing dependence on external heating utilities and minimizing unnecessary heat losses. Simulation results reveal a significant reduction in total energy demand, with overall heat consumption lowered by 507,602.4 kJ/h relative to the original system. These findings highlight the potential of strategic heat integration to markedly enhance the energy performance of acetaldehyde production. In conclusion, incorporating a heat exchanger prior to downstream heating units offers a practical and effective means of optimizing energy use while promoting more efficient and environmentally responsible process designs. Copyright © 2026 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).